113k views
5 votes
Solve for y: 2(3y + 5) = 3(5y + 3).
The solution is y =
The solution is

User Bwc
by
4.6k points

2 Answers

7 votes

Answer:y=1/9

Explanation:

Remove the parenthesis, move the terms, collect like terms, calculate, divide both sides

User Ben Bracha
by
4.5k points
2 votes

Answer:

y =
(1)/(9)

Explanation:

Given

2(3y + 5) = 3(5y + 3) ← distribute parenthesis on both sides

6y + 10 = 15y + 9 ( subtract 6y from both sides )

10 = 9y + 9 ( subtract 9 from both sides )

1 = 9y ( divide both sides by 9 )


(1)/(9) = y

User Yahe
by
4.9k points